Evaluation of the Human Resources Training and Development Program for Performance and Productivity Improvement (Case Study at Perumda Tirta Manuntung Balikpapan) - Fernando Febryan; Muafi Muafi (Cita Konsultindo Research Center, 2023)
Perumda Tirta Manuntung Balikpapan is a clean water and sanitation provider organization that recognizes the importance of human resources as the main asset in achieving company goals. Therefore, the company has implemented a human resource training and development program that includes technical, soft skills, leadership, and career training. Evaluation of the program is needed to assess its impact on employee performance and productivity, as well as to design more effective programs in the future. The research method used is a case study through interviews, observation, and documentation to provide valuable input for companies. The author knows the types of training and HR development, program evaluation measuring tools, constraints and strategies for handling them, impact on employees, next steps, and participant recommendations to increase the effectiveness of HR training and development programs at Perumda Tirta Manuntung Balikpapan. Training programs and human resource development at Perumda Tirta Manuntung Balikpapan consists of In House Training and Competency Training. The two programs are evaluated by evaluating performance indicators and evaluating employee training. The results of the evaluation show the significant involvement of the participants in providing reports on the results of the training activities. The company takes a methodical approach by communicating formal deadlines to address the problem of late reports. Organizers also pay attention to participants' expectations in determining training schedules and qualifications, to increase program effectiveness.